2004
DOI: 10.1007/s00259-003-1410-z
|View full text |Cite
|
Sign up to set email alerts
|

DMSA study performed during febrile urinary tract infection: a predictor of patient outcome?

Abstract: Technetium-99m dimercaptosuccinic acid (DMSA) study has been advocated as a method for the assessment of renal sequelae after acute febrile urinary tract infection (UTI). However, it is not known whether DMSA scintigraphy performed during acute UTI has any prognostic value for outcome assessment. The objective of this study was to evaluate the usefulness of DMSA scintigraphy performed during UTI as a predictor of patient outcome, to identify children at risk of events [vesico-ureteral reflux (VUR) or recurrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 29 publications
3
46
1
3
Order By: Relevance
“…[17][18][19] They demonstrated the efficiency of this imaging modality for clinical use in comparison with conventional imaging techniques such as ultrasound, CT and MRI methodology. Comparatively, ultrasound has not a high sensitivity for APN and spiral CT and MRI, with equal sensitivity, are not routinely recommended.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] They demonstrated the efficiency of this imaging modality for clinical use in comparison with conventional imaging techniques such as ultrasound, CT and MRI methodology. Comparatively, ultrasound has not a high sensitivity for APN and spiral CT and MRI, with equal sensitivity, are not routinely recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, dado que habitualmente recibimos a la mayoría de los pacientes con ITU del Hospital para completar su estudio y que excluimos a los pacientes con uropatías conocidas, la distribución de los grados de RVU fue similar a la observada por otros autores. 35 Por otro lado, el hecho de que ningún paciente del grupo evaluado luego de la aparición de las guías de 2011 se haya estudiado por ITU atípica tal vez refleje un inadecuado reconocimiento de esta, lo que retrasa su referencia para estudio.…”
Section: Discussionunclassified
“…cases of febrile UTI and high-degree VUR. On the other hand, the incidence of renal scarring ranges from 15% to 62% (9)(10)(11)(12)(13) . In the present review, the authors' have not found in the Brazilian literature any study aimed at determining the prevalence of APN and incidence of renal scarring in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…For occurrence of APN, for example, some studies report a frequency of 26% (9) , while others report 57% prevalence of renal infection in the investigated population (10) . Most studies utilize renal scintigraphy with DMSA for the diagnosis of such conditions.…”
Section: Introductionmentioning
confidence: 99%